The City Crown, or the 'Social Sublime' (diségno, 2023)
I have read La corona della città (The City Crown, in english) (fig. 1) three times. The first time –but I don’t know if it can be considered valid– as a student, at the invitation of a Composition professor, who suggested: “Stop at Quaroni’s introduction, everything else is superfluous”. The complete reading took place a few years later, during my PhD years. I found the book flowing, at times amusing, thanks to the radical positions expressed in vehement tones. [read more]